Computer fitness how to work comfortably, productively and safely - Cornell, Dixie (Eau Claire, Wi. Televideo Productions, 1992)
Demonstrates the habits and concepts of good posture in using computers.
VHS.
Narrator, Bart Simon.
Keywords: Posture; Computers